THE EFFECT OF BABY MASSAGE ON THE SLEEP QUALITY OF 3-12 MONTHS BABIES IN PRIVATE MIDWIVE JAMBI CITY - Atika Fadhilah Danaz Nasution; Nuraidah; Imelda (OPI Napoli, 2021)
Introduction: Sleep needs in infants 3-12 months are not only in terms of quantity but also quality. Good quality sleep provides benefits to the fulfilment of physical and psychological needs. One method of meeting these needs is baby massage. A common reason for mothers to give baby massages is the child's habit of fussing at night and often waking up, and they say that after the massage, their child becomes calm at night. This study aims to analyze the effect of baby massage on the sleep quality of infants aged 3-12 months at private midwife Muji Kenali Asam in Jambi City. Material and Methods: This pre-experimental study consisted of a one-group pretest-posttest design for a group of 68 infants aged 3-12 months. The questionnaire was compiled into a google form, and the link was distributed to each mother. Data processing consists of editing, coding, tabulating and statistical tests (Wilcoxon test) at the limit of significance value of 0.05. Results: The study results that can be described are that most of the sleep quality of infants aged 3-12 months before the intervention was sufficient at 45.6%, and for poor quality, it was 27.9%. After the intervention, most infants aged 3-12 months were good in sleep quality by 45.5% and sufficient sleep quality by 52.9%. The results of the Wilcoxon test revealed the effect of infant massage on infant sleep quality with a significance value of p-value = 0.001. Conclusion: Baby massage tends to improve the baby's sleep quality. Therefore Midwifery students need to acquire baby massage skills and promote the method to mothers, particularly those with babies 3-12 months.